양면형 BIPV 시스템의 설치환경에 따른 발전특성 분석 - 강준구(Jun Gu Kang); 김진희(Jin Hee Kim); 김준태(Jun Tae Kim) (Current Photovoltaic Research, 2015)
BIPV system is one of the best ways to harness PV module. The BIPV system not only produces electricity, but also acts as a building envelope. Thus, it has the strong point of increasing the economical efficiency by applying the PV modules to the buildings. Bifacial solar cells can convert solar energy to electrical energy from both sides of the module. In addition, it is designed as 3 busbar layout which is the same with ordinary mono-facial soalr cells. Therefore, many of the module manufacturers can easily produce the bifacial solar cells without changing their manufacturing equipment. Moreover, bifacial BIPV system has much potential in building application by utilizing glass to glass structure. However, the performance of bifacial solar cells depends on a variety of factors, ranging from the back surface to surrounding conditions. Therefore, in order to apply bifacial solar cells to buildings, an analysis of bifacial PV module performance should be carried out that includes a consideration of various design elements, and reflects a wide range of installation conditions. As a result it found that the white insulation reflector type can improve the performance of the bifacial BIPV system by 16%, compared to the black insulation reflector type. The performance of the bifacial BIPV was also shown to be influenced by inclination angle, due to changes in both the amount of radiation captured on the front face and the radiation transmitted to the rear face through the transparent space. In this study is limited design condition and installation condition. Accordingly follow-up researches in this part need to be conducted.